Estructuras morfológicas y modulares con base a las expresiones, de las Nacionalidades de Sucumbíos - Monar Machoa, Erika Jessenia (2021)
Graphic Design and the study of Andean Design allow us to perform iconographic research on our culture, customs and traditions, transmitting it through visual communication. Allowing to update the information to generate new proposals that help to spread our ancestral legacy. This research had as its main objective the study of the cultural expressions of the nationalities of the Sucumbíos province, guided by the theory and methodological processes of Graphic Design and Andean Design. The iconography that was evidenced in the four nationalities was analyzed: Shuar, Kichwa, A’I Cofán and Siekopai. The cultural expressions studied were: clothing, handicrafts and face painting; the research process was approached from an ethnographic, descriptive and analytical approach. In this sense, important aspects were determined to be able to develop morphological and modular proposals. The semiotic analysis of cultural expressions started from a process of abstraction, analysis of descriptive Andean syntax, analytical Andean semantics and interpretive Andean pragmatics, as part of the process an experimentation with the interconnection of forms (Interconnection, Chaining and Interlacing) was carried out. To later experiment based on Fractal Geometry, obtaining Modules and Supermodules; These modules resulting from the experimentation were applied in a textile collection inspired by the characteristic features of the traditional clothing of the four nationalities, in order to present modern textile proposals with cultural motifs representative of the Sucumbíos nationalities, to generate a feeling of appropriation cultural in the new generations.